Pelatihan Perawatan Kaki pada Kader Posyandu Lansia untuk Meningkatkan Pengetahuan Kader dalam Pencegahan Ulkus Kaki Diabetikum di Wilayah Puskesmas Sekaran - Diana Dayaningsih; Novita Wulan Sari; Jihar Muhammad Pratama; Rahayu Wulan Maulidina; Yusril Azzuri Indrasta (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetic ulcers are a serious complication of diabetes mellitus that arise from damage to blood vessels and nerves due to uncontrolled blood sugar levels. This condition causes wounds, especially on the underside of the big toe or the soles of the feet. According to data from the Central Java Provincial Health Office, Semarang City ranks third out of 35 cities/regencies with a high number of diabetes cases. In 2022, 17,037 cases of diabetes were recorded, an increase from 15,250 cases the previous year. Nationally, according to the 2024 Basic Health Research (Riskesdas), diabetic ulcers are one of the leading causes of death across all age groups, accounting for 15.4%. In the 55–64 age group, the figure reaches 26.8%, in both urban and rural areas, while the youngest stroke cases are found in the 18–24 age group. Promotive efforts to control diabetic ulcers include optimal foot care for elderly people with diabetes, regular glycemic monitoring, and foot exercises to prevent new ulcers and reduce the risk of recurrence. Furthermore, health education involving elderly Posyandu (Integrated Service Post) cadres and their families is also an important strategy in reducing the incidence. The role of elderly Posyandu cadres is crucial, as they are expected to have adequate skills and understanding of foot ulcer prevention through education and practical foot care. The training provided to elderly Posyandu cadres has proven to be successful without significant obstacles. The enthusiasm of the community, particularly the cadres and their families, was high, participating in the activity until completion. This demonstrates a growing awareness of the importance of diabetic ulcer prevention, which is expected to reduce the number of cases in elderly people with diabetes and improve their quality of life.